Action observation in infancy: Implications for neuro-rehabilitation - Burzi, V.; Tealdi, G.; Boyd, Roslyn; Guzzetta, A. (Wiley-Blackwell Publishing Ltd., 2016)
© 2016 Mac Keith Press.Action observation therapy has been found to be effective in improving hand motor function in both adults with stroke and children with unilateral cerebral palsy. We here propose a provocative hypothesis arguing that the same therapy might be effective in very early intervention in infants with unilateral or asymmetric brain damage, but through a different underlying mechanism. If the activation of motor networks induced in infancy by action observation enhances the excitability of the damaged sensorimotor cortex, it could also accelerate the maturation of the corticospinal tract and the adaptive shaping of the spinal motor circuits. This hypothesis should be explored carefully in prospective studies and, if confirmed, might support the use of action observation therapy at a much earlier time than experimented so far. What this paper adds: A revision of the literature on AOT in children and adults with unilateral brain damage. The discussion of possible mechanisms of AOT in brain damaged individuals, when applied in early infancy.